2006
DOI: 10.1097/01.mcg.0000225588.63083.c9
|View full text |Cite
|
Sign up to set email alerts
|

Critical Care Nutrition: Getting Involved as a Gastrointestinal Endoscopist

Abstract: The route, timing, and volume of enteral feeding delivered to a patient in the intensive care unit have a profound effect on clinical outcome. At the height of critical illness, problems with ileus, aspiration, and the systemic inflammatory response syndrome make the provision of enteral nutrients a difficult and somewhat risky endeavor. The gastrointestinal endoscopist has the technical skills to place feeding tubes deep within the jejunum and an underlying expertise in gut physiology to monitor patients effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 55 publications
(117 reference statements)
0
13
0
Order By: Relevance
“…24 In patients with ileus, EN is encouraged by accessing the small bowel, decompressing the stomach, and initiating feeds to stimulate promotility agents. 19 Many of our respondents indicated that ileus is an absolute contraindication to enteral feeding.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…24 In patients with ileus, EN is encouraged by accessing the small bowel, decompressing the stomach, and initiating feeds to stimulate promotility agents. 19 Many of our respondents indicated that ileus is an absolute contraindication to enteral feeding.…”
Section: Discussionmentioning
confidence: 93%
“…33 Assessing and promoting tolerance may be the most important aspect of monitoring the patient on EN. 19 There was a large standard deviation in responses regarding an acceptable GRV in a tube-fed patient, indicating discordance in this area. Although GRVs have poor validity as a marker for risk of aspiration in critically ill patients, 34 they continue to be used in nutrition algorithms and are likely to be the practice of many ICUs.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…[345] The value of EN is further supported by studies which have shown that nutritional deficit due to delayed initiation has an adverse effect, whereas institution of protocols to increase delivery often improves patient outcome. [6789] It has been noted that the value of EN is closely related to disease severity; greater the severity of the disease, higher the benefit of EN. [10111213] Optimal nutrition support during critical illness requires individualized assessment of timing, route and quantity of nutrients and protocolized feeding.…”
Section: Introductionmentioning
confidence: 99%